(untitled) (Nexo Revista Científica, 2021)
The present study was focused on order to characterize the edaphic macrofauna in three different agroforestry systems: CMIEA: Coffee, musaceae, Inga, Erithryna and trees, CIE: Coffee, Inga, Erithryna and trees and CA: Coffee and trees in dry season and rainy season. Each system had 900m2, they had approximately 6 tree species per system. 32 monoliths were taken per season, and this was divided into four strata (litter, 0 to 10cm, 10 to 20cm and 20 to 30cm) with the method recommended by the Tropical Soil Biology and Fertility Program. The macrofauna was preserved in 70% alcohol, except for the worms that were preserved with 4% formalin and were transferred to the Entomology Laboratory of the Department of Agroecology of UNAN-León for their respective construction. The results show the highest values of abundance occurred in the rainy season (391 individuals) and in the dry season (324 individuals). The highest abundance was found in the CMIEA system (162 individuals) in the rainy season and minimum in the CA system (91 individuals) in the dry season. The Shannon diversity index was highest in the CA system (2.73) in the dry season and lowest in the CIE system (1.44). The arrangements of the agroforestry systems do not influence the abundance of the macrofauna, however, it favors the presence of Philoscia species and soil worms order Haplotaxida.